Tuning the Porosity and Photocatalytic Performance of Triazine-Based Graphdiyne Polymers through Polymorphism - Schwarz, Dana; Acharjya, Amitava; Ichangi, Arun; Kochergin, Yaroslav S; Lyu, Pengbo; Opanasenko, Maksym V; Tarábek, Ján; Vacek Chocholoušová, Jana; Vacek, Jaroslav; Schmidt, Johannes; Čejka, Jiří; Nachtigall, Petr; et al. (ChemSusChem, 2019)
Crystalline and amorphous organic materials are an emergent class of heterogeneous photocatalysts for the generation of hydrogen from water, but a direct correlation between their structures and the resulting properties has not been achieved so far. To make a meaningful comparison between structurally different, yet chemically similar porous polymers, two porous polymorphs of a triazine-based graphdiyne (TzG) framework are synthesized by a simple, one-pot homocoupling polymerization reaction using as catalysts CuI for TzGCu and PdII /CuI for TzGPd/Cu . The polymers form through irreversible coupling reactions and give rise to a crystalline (TzGCu ) and an amorphous (TzGPd/Cu ) polymorph. Notably, the crystalline and amorphous polymorphs are narrow-gap semiconductors with permanent surface areas of 660 m2 g-1 and 392 m2 g-1 , respectively. Hence, both polymers are ideal heterogeneous photocatalysts for water splitting with some of the highest hydrogen evolution rates reported to date (up to 972 μmol h-1 g-1 with and 276 μmol h-1 g-1 without Pt cocatalyst). Crystalline order is found to improve delocalization, whereas the amorphous polymorph requires a cocatalyst for efficient charge transfer. This will need to be considered in future rational design of polymer catalysts and organic electronics.
Keywords: carbon; semiconductors; porous polymers; photocatalysis; covalent organic frameworks